2019
DOI: 10.26444/aaem/89733
|View full text |Cite
|
Sign up to set email alerts
|

Indications for sexology consultation in women after surgical treatment due to breast cancer

Abstract: Jach R. Indications for sexology consultation in women after surgical treatment due to breast cancer. Ann Agric Environ Med. doi: 10.26444/aaem/89733 Abstract Introduction and objectives. Surgical treatment due to brest cancer have an impact on women sexuality. There is a need for research about effective indications for sexology consultation in women after such treatment. The aim of this study is to determine the indications for sexology consultation in women after surgical treatment for breast cancer. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
(24 reference statements)
0
7
0
4
Order By: Relevance
“…Este mesmo estudo afirmou que Pacientes que tiveram a reconstrução da mama após a mastectomia relataram melhor função sexual e menos sintomas depressivos. Onde cerca de 25% a 90% das mulheres após da mama apresentam alterações sexuais e mentais, apresentando quadros de depressão e problemas na relação com um parceiro (Streb et al, 2019) Percebeu-se que passar pela experiência do câncer requer abdicar muito e estar pronto a dedicação e apoio do cônjuge. Os estudos apontam que os companheiros têm apresentado posturas despreparadas, ocasionando sentimento de rejeição e afastamento em suas mulheres, prejudicando ainda mais no processo de manutenção da autoestima (Oliveira, Silva & Prazeres, 2017;Varela et al, 2017;Ghizzani, Bruni &Luisi, 2018).…”
Section: Categoria 2 -O Relacionamento Afetivo-sexualunclassified
“…Este mesmo estudo afirmou que Pacientes que tiveram a reconstrução da mama após a mastectomia relataram melhor função sexual e menos sintomas depressivos. Onde cerca de 25% a 90% das mulheres após da mama apresentam alterações sexuais e mentais, apresentando quadros de depressão e problemas na relação com um parceiro (Streb et al, 2019) Percebeu-se que passar pela experiência do câncer requer abdicar muito e estar pronto a dedicação e apoio do cônjuge. Os estudos apontam que os companheiros têm apresentado posturas despreparadas, ocasionando sentimento de rejeição e afastamento em suas mulheres, prejudicando ainda mais no processo de manutenção da autoestima (Oliveira, Silva & Prazeres, 2017;Varela et al, 2017;Ghizzani, Bruni &Luisi, 2018).…”
Section: Categoria 2 -O Relacionamento Afetivo-sexualunclassified
“…After breast cancer diagnosis and treatment, all aspects of sexual function including libido, arousal, and orgasm are often deteriorated. Patients experience dyspareunia and negative mental experiences such as negative body image, loss of femininity, concerns about infertility, lack of sexual attractiveness, depression, and anxiety, leading to reduced sexual satisfaction and finally discontinuing sexual relations [ 6 , 7 ]. For example, a study in Iran showed that sexual dysfunction is more common in breast cancer survivors than in healthy women.…”
Section: Introductionmentioning
confidence: 99%
“…After Breast cancer diagnosis and treatment, all aspects of sexual function including libido, arousal, and orgasm are often deteriorated. Patients experience dyspareunia and negative mental experiences such as negative body image, loss of femininity, concerns about infertility, lack of sexual attractiveness, depression, and anxiety leading to reduced sexual satisfaction and nally discontinuing sexual relations [6,7]. Similarly, a study in Iran showed that sexual dysfunction is more common in breast cancer survivors compared to healthy women.…”
Section: Introductionmentioning
confidence: 99%